2019
DOI: 10.1029/2019gl084377
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Volcanic Aerosol Meridional Structure on Monsoon Responses over the Last Millennium

Abstract: Monsoon responses to eruptions over the last millennium (LM) are examined in an ensemble of climate simulations as a function of eruption hemisphere. A composite analysis reveals a particularly strong sensitivity of monsoon rainfall in the year following Northern Hemisphere (NH) extratropical eruptions. Additional analysis focusing on the 18th century eruption of Mt. Laki and idealized simulations representing an analogue Southern Hemisphere eruption (SH‐Laki) reveal monsoon responses that are approximately sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
3
12
0
1
Order By: Relevance
“…For context, 4 °C cooling is approximately four times the magnitude of global warming from 1880 to 2012 (United Nations Intergovernmental Panel on Climate Change Fifth Assessment Report). The muted cooling in the SH, which is consistent with prior work (31,44,54,55), highlights the role of the ocean in modulating the cooling (45,56) from the stratospheric volcanic aerosol cloud. In addition, the fact that the aerosol cloud is located over the NH in the majority of our simulations (SI Appendix, Figs.…”
Section: Regional Temperature Response Patterns and The Role Of The Ocean In Modulating The Climate Responsesupporting
confidence: 85%
“…For context, 4 °C cooling is approximately four times the magnitude of global warming from 1880 to 2012 (United Nations Intergovernmental Panel on Climate Change Fifth Assessment Report). The muted cooling in the SH, which is consistent with prior work (31,44,54,55), highlights the role of the ocean in modulating the cooling (45,56) from the stratospheric volcanic aerosol cloud. In addition, the fact that the aerosol cloud is located over the NH in the majority of our simulations (SI Appendix, Figs.…”
Section: Regional Temperature Response Patterns and The Role Of The Ocean In Modulating The Climate Responsesupporting
confidence: 85%
“…Liu et al (2016) discovered that the monsoon precipitation in one hemisphere is substantially increased by the other hemispheric volcanic eruptions using the Community Earth System Model (CESM), and this volcano-induced remote enhancement is mainly through circulation changes. Similarly, recent studies using the CESM1-CAM5 and proxy data found a weakened (strengthened) Northern (Southern) Hemisphere monsoon following northern eruptions (Fasullo et al 2019;Meng et al 2019). They suggested that the dynamic process associated with atmospheric circulation change plays an essential role in precipitation response.…”
Section: Introductionmentioning
confidence: 68%
“…These shortcomings are known to impact regional features of the precipitation distribution and its response to forcing. Other aspects however, such as land-ocean contrasts and simulated increase in ensemble spread in large-scale precipitation metrics are less sensitive to such effects, as they are rooted in energetically constrained responses (Fasullo et al, 2019) and thermodynamic contrasts between land and ocean (Fasullo, 2012). When considering regional precipitation responses over 20-year time periods, large simulation ensembles with many volcanic forcing evolutions are needed to sufficiently sample potential volcanism and robustly detect responses in the presence of large regional internal climate variability, partly related to ENSO (Paik et al, 2020).…”
Section: Summary and Discussionmentioning
confidence: 99%